Pergeseran Gaya Kampanye Politik dari Media Konvensional ke Narasi Mikro-Influencer - Putri Lailatul Ramadhani; Ruhbatun Nafisah; Izmiyatul Aisyah; Wahyu Fitri Ega; Shofi Wulandari (Prisani Cendekia Institute, 2026)
This article examines the transformation of political campaign styles from conventional mass media to micro-influencer-driven narratives within the context of digital political communication. Using a Systematic Literature Review (SLR) approach guided by the PRISMA protocol and reported through the SPAR-4-SLR framework, this study synthesizes findings from 20 peer-reviewed journal articles indexed in the Scopus database published between 2016 and 2026. Keywords used include digital political communication, strategy political communication, and media political campaigns. The review reveals a significant shift toward personalized, narrative-based, and emotionally driven campaign strategies facilitated by micro-influencers, particularly in engaging Generation Z voters. While this shift enhances political participation and relatability, it also raises concerns regarding transparency, ethical campaigning, and democratic deliberation. The findings suggest that micro-influencers play a crucial role in shaping public opinion and influencing voter behavior, but also highlight the need for greater transparency and accountability in digital political communication. The study concludes that the use of micro-influencers in political campaigns is a double-edged sword, offering both opportunities and challenges for democratic engagement and deliberation.